Pengaruh Metode Brainstorming Terhadap Kemampuan Berpikir Kreatif Siswa Dalam Mata Pelajaran IPA Kelas V UPT SPF SD Inpres Bontomanai - Miftahul Rahmi; Nasrah Nasrah; Amri Amal (Journal on Education, 2023)
This study aims to determine the level of creative thinking skills of fifth grade UPT SPF SD Inpres Bontomanai students in science learning after using the Brainstorming method and the effect of using the Brainstorming method on creative thinking skills in science learning for fifth grade students UPT SPF SD Inpres Bontomanai. This study used the Quasi Experimental Design research method. The population in this study were all fifth grade students at UPT SPF SD Inpres Bontomanai. The sampling technique used is the total sampling technique or saturated samples with samples from the experimental class and the control class. The instrument used is a test instrument in the form of essay questions to measure students' creative thinking abilities with the Pretest - Posttest Control Group Design. Based on the results of the research, it was shown that the level of students' creative thinking ability in science in the experimental class, which after using the Brainstorming method, was 66.67% in the creative category, while in the control class, 57.12% was obtained in the very less creative category. Meanwhile, the effect of using the brainstorming method on creative thinking skills in science learning for fifth grade students of UPT SPF SD Inpres Bontomanai from the results of managing the hypothesis obtained Sig (2.Tailed) = 0.000 meaning that H0 is rejected because Sig (2.Tailed) < α or (0.000 < 0.05). H1 is accepted because Sig (Tailed) > α or (0.544 > 0.05) with the results of the T test analysis, Sig < ttable or (0.544 < 1.683). So the effect of using the Brainstorming method on the ability to think creatively in science learning for fifth grade students is influential at UPT SPF SD Inpres Bontomanai.